Flexible electrode and diaphragm integrated structure design for alkaline electrolyzed water and preparation method of flexible electrode and diaphragm integrated structure design
Through the integrated structural design of flexible electrodes and diaphragms, the problems of low electrode efficiency and insufficient diaphragm performance in alkaline electrolytic water technology are solved, efficient and stable hydrogen energy conversion and cost reduction are achieved, and new hydrogen production is provided for alkaline electrolytic water. technical route.
Patent Information
- Application Number
- CN202411610551.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing alkaline electrolytic technology, the nickel-based electrode efficiency is low and the polyphenylene sulfide separator has problems such as poor hydrophilicity, high surface resistance and poor gas barrier, resulting in insufficient hydrogen production efficiency and equipment stability.
The integrated structure design of flexible electrode and separator is adopted, and the sandwich structure membrane electrode is prepared by phase conversion casting and hot pressing method. A high-concentration potassium hydroxide solution is used as the electrolyte. The cathode produces hydrogen, the anode produces oxygen, and the separator is separated to achieve Gas circulation collection. The structure includes a flexible cathode layer, a composite separator layer and a flexible anode layer, using structure or conductive polymer and electrocatalytic material powders such as transition metals, and the separator layer contains alkali-resistant polymers and nano-inorganic ceramic particles.
It realizes efficient and stable hydrogen energy conversion, reduces costs, improves the hydrogen evolution/oxygen evolution catalytic performance of the electrode, avoids the puncture of the separator, and provides a new technology route for alkaline electrolytic hydrogen production.
Smart Images

Figure CN119265596A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of hydrogen production by water electrolysis, and in particular to a flexible electrode and diaphragm integrated structure design for alkaline water electrolysis and a preparation method thereof. Background Art
[0002] In order to cope with climate change and environmental pollution, it is urgent to reduce dependence on traditional fossil energy and promote the transformation of energy structure towards clean, low-carbon and sustainable direction. Hydrogen has the advantages of high energy density and pollution-free combustion products, and is regarded as an important component of the future energy system. The continuous progress of the power system, including the large-scale application of renewable energy generation (such as solar energy, wind energy, etc.), provides a rich source of electricity for hydrogen production by electrolysis of water. The principle of water electrolysis was discovered as early as the 19th century. After years of research and development, water electrolysis technology has been continuously improved and optimized. The development of new electrode / membrane materials has improved the efficiency of water electrolysis, reduced costs, and enhanced the stability and durability of water electrolysis equipment.
[0003] The mainstream technology route in the current domestic electrolytic water market is alkaline electrolysis (ALK) technology, which has completed the commercialization process and occupies a dominant position in the market, while proton exchange membrane electrolysis (PEM) technology is still in the early stages of commercialization due to cost constraints. In addition, solid oxide electrolysis and anion exchange membrane electrolysis technologies are still in the research and development stage. Since ALK has lower technical requirements and costs than PEM and a larger single-tank scale, it is currently the first choice for electrolytic water hydrogen production technology. The ALK hydrogen production electrolyzer includes electrodes, electrolytes, and diaphragms. The electrochemical reaction on the electrodes determines the efficiency of hydrogen production, and currently most of them use cheap nickel-based electrodes. The main functions of the diaphragm include allowing the free movement of ions in the electrolyte and isolating the hydrogen and oxygen produced during the electrolysis of water. At present, most ALK commercial diaphragms use polyphenylene sulfide (PPS) diaphragms, but PPS diaphragms have problems such as poor hydrophilicity, high surface resistance, and poor gas barrier properties. Summary of the invention
[0004] In view of the shortcomings of the existing ALK hydrogen production technology, the present invention provides a flexible electrode and diaphragm integrated structure design and its preparation method. The present invention adopts phase conversion casting combined with hot pressing to prepare a sandwich structure membrane electrode as the electrode and diaphragm of ALK, and uses a high concentration potassium hydroxide solution as the electrolyte. During operation, hydrogen is generated on the cathode and oxygen is generated on the anode. The two gases are separated by the diaphragm and enter the gas collection chamber with the electrolyte circulation.
[0005] One of the purposes of the present invention is to provide a flexible electrode and diaphragm integrated structure, comprising a flexible cathode layer, a composite diaphragm layer and a flexible anode layer connected in sequence. The flexible electrode layer comprises a structural or conductive polymer and an electrocatalytic material powder such as a transition metal, and the diaphragm layer comprises an alkali-resistant polymer and nano inorganic ceramic particles.
[0006] According to the flexible electrode and diaphragm integrated structure provided by the present invention, the flexible electrode layer contains 5-20% of polymer by mass, and 50-70% of transition metal powder by mass. The composite diaphragm layer contains 5-20% of polymer by mass, and 10-80% of inorganic nano-ceramic powder by mass.
[0007] According to the flexible electrode and diaphragm integrated structure provided by the present invention, the high molecular polymer is one or more of polysulfone, polyethersulfone, polyvinylpyrrolidone, polyphenylene sulfide, polyaniline, polypyrrole, and polythiophene.
[0008] According to the flexible electrode and diaphragm integrated structure provided by the present invention, the transition metal powder is one or more of metal powders having hydrogen or oxygen evolution capabilities such as nickel powder, cobalt powder, iron powder, or carbide / oxide ceramic powders containing metal elements such as nickel, cobalt, and molybdenum; the size is about 200 mesh.
[0009] According to the flexible electrode and diaphragm integrated structure provided by the present invention, the inorganic nano-ceramic powder is a combination of one or more of zirconium dioxide, titanium dioxide and silicon dioxide; and the size is 50-1000nm.
[0010] The second object of the present invention is to provide a method for preparing the flexible electrode and diaphragm integrated structure as described in one of the above objects, the preparation method comprising the following steps:
[0011] (1) A high molecular polymer (such as polysulfone, polyethersulfone, polyaniline, etc.) and an organic solvent (such as N-methylpyrrolidone, N,N-dimethylformamide) are stirred uniformly to form a precursor slurry;
[0012] (2) adding transition metal or carbide / oxide powder (such as nickel powder, cobalt powder, molybdenum carbide, nickel cobalt oxide) or inorganic nano-ceramic powder (such as zirconium dioxide, titanium dioxide) to the precursor slurry, respectively, and ball milling for 48 hours to fully mix them to obtain electrode and diaphragm slurries, respectively;
[0013] (3) adjusting the height of the scraper of the tape casting machine, respectively coating the electrode and diaphragm slurries of different thicknesses on the glass plate, and then immersing them in water or ethanol solvent for phase inversion, and finally obtaining a flexible electrode green body with a thickness of 10-500 μm and a diaphragm green body with a thickness of 200-800 μm;
[0014] (4) After taking out the green body, drying it at 80-150° C., and hot pressing it at 80-150° C. and 0.5-10 MPa for 5-10 min, a flexible electrode and diaphragm integrated structure of cathode / diaphragm / anode is obtained.
[0015] As a preferred technical solution of the present invention, the solvent in step (3) is ethanol aqueous solution, and the phase conversion time is 4-24h.
[0016] The present invention proposes a flexible electrode and diaphragm integrated structure design for alkaline water electrolysis and a preparation method thereof, which has the following beneficial effects:
[0017] 1. The process is simple to implement, the conditions are easy to meet, the application range is wide, and it can be used for composite diaphragms / electrodes of all systems.
[0018] 2. The hydrogen / oxygen evolution catalytic performance of the electrode can be regulated by changing the type and content of the transition metal or its carbide / oxide powder.
[0019] 3. The present invention can achieve efficient and stable hydrogen energy conversion without side reactions under high voltage and high current density.
[0020] Compared with the prior art, the present invention adopts an integrated structure to make the catalyst, electrode and diaphragm into a whole, and the prepared flexible electrode can prevent the diaphragm from being punctured. The flexible electrode and diaphragm integrated structure prepared by the present invention is used for alkaline water electrolysis at a lower cost and with stable performance, providing a new feasible idea and technical route for alkaline water electrolysis hydrogen production and other electrolysis processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions in the present application or related technologies, the drawings required for use in the embodiments or related technical descriptions are briefly introduced below. Obviously, the drawings described below are only embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 Schematic diagram of the integrated structure of the flexible electrode and the diaphragm obtained in the embodiment of the present invention;
[0023] Figure 2 This is a surface image of the integrated structure of the flexible electrode and diaphragm obtained in Example 1;
[0024] Figure 3 This is a cross-sectional physical picture of the integrated structure of the flexible electrode and the diaphragm obtained in Example 1;
[0025] Figure 4 This is a scanning electron microscope image of the surface of the integrated structure of the flexible electrode and diaphragm obtained in Example 1;
[0026] Figure 5 This is a scanning electron microscope image of the cross section of the flexible electrode and diaphragm integrated structure obtained in Example 1;
[0027] Figure 6 This is a polarization curve diagram of the flexible electrode and diaphragm integrated structure obtained in Example 1 used in the alkaline water electrolysis process;
[0028] Figure 7 The flexible electrode and diaphragm integrated structure obtained in Example 1 is 800 mA cm -2 Stability test diagram under current density. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The technical solution protected by the present invention will be described in detail below.
[0031] Example 1
[0032] A: Use a tray balance to weigh 1g of polyvinyl pyrrolidone (PVP), 4g of polyethersulfone (PESf) and 25g of N-methylpyrrolidone (NMP) solvent, and add them to ball mill A; weigh the same amount of the above three substances and add them to ball mill B. After ball milling and stirring for 2h, a uniform and transparent polymer solution with a mass fraction of 17% is obtained.
[0033] B: Add 70g nickel powder to tank A and 70g nano zirconium dioxide to tank B, and stir by ball milling for 48h to fully mix them. The mass fraction of inorganic powder is 70%.
[0034] C: Place the slurry in tank A on a glass plate, adjust the distance between the scraper and the glass plate, and use the scraper to apply the coating to obtain an electrode coating with a thickness of 10-500μm. Place the slurry in tank B on another glass plate, and repeat the above operation to obtain a separator coating with a thickness of 200-800μm.
[0035] D: The above coatings are placed in a water bath and allowed to stand for 4-24 hours, so that the organic solvent in the coatings is fully mixed with water, phase separation occurs, and finally solidified to obtain flexible electrodes and separator green bodies, respectively. The temperature of the water bath is 20°C.
[0036] E: The green body is taken out of the water and dried at 150°C, cut into electrodes and diaphragms of appropriate sizes, and then hot-pressed at 80-150°C and 0.5-10 MPa for 5-10 min to obtain a flexible electrode and diaphragm integrated structure of cathode / diaphragm / anode in sequence.
[0037] The surface and cross-sectional images of the flexible electrode and diaphragm integrated structure prepared in Example 1 are as follows: Figure 2 , Figure 3 The surface morphology and cross-sectional morphology of the integrated structure of flexible electrode and diaphragm are shown in Figure 4 , Figure 5 As shown; the polarization curve of the flexible electrode and diaphragm integrated structure used in the alkaline water electrolysis process is shown Figure 6 As shown in the figure; the flexible electrode and diaphragm integrated structure at 800mA cm -2 The stability test results under current density are as follows Figure 7 shown.
[0038] Example 2
[0039] A: 1.5 g of polyvinyl pyrrolidone (PVP), 0.5 g of polyaniline (PANI), 6 g of polysulfone (PSU) and 25 g of N-methylpyrrolidone (NMP) solvent were weighed on a pan balance and added to ball mill A; 2 g of polyvinyl pyrrolidone (PVP), 6 g of polysulfone (PSU) and 25 g of N-methylpyrrolidone (NMP) solvent were weighed and added to ball mill B. After ball milling and stirring for 2 h, a uniform and transparent polymer solution with a mass fraction of 24% was obtained.
[0040] B: Add 60g of nickel powder to tank A and 60g of nano zirconium dioxide to tank B, and stir by ball milling for 48h to fully mix them. The mass fraction of inorganic nano ceramic powder is 64.5%.
[0041] C: Place the slurry in tank A on a glass plate, adjust the distance between the scraper and the glass plate, and use the scraper to apply the coating to obtain an electrode coating with a thickness of 10-500μm. Place the slurry in tank B on another glass plate, and repeat the above operation to obtain a separator coating with a thickness of 200-800μm.
[0042] D: The above coatings are placed in an ethanol bath and allowed to stand for 4-24 hours, so that the organic solvent NMP in the coatings is fully mixed with the ethanol, phase separation occurs, and finally solidification is performed to obtain the flexible electrode and the separator green body, wherein the temperature of the ethanol bath is 20°C.
[0043] E: The green body is taken out from the ethanol and dried at 150°C, cut into electrodes and diaphragms of appropriate sizes, and then hot-pressed at 80-150°C and 0.5-10MPa for 5-10min to obtain a flexible electrode and diaphragm integrated structure of cathode / diaphragm / anode in sequence.
[0044] Example 3
[0045] A: Weigh 4g of polyvinyl pyrrolidone (PVP), 7g of polysulfone (PSU) and 25g of N,N-dimethylformamide (DMF) solvent using a tray balance and add them to ball mill A; weigh the same amount of the three substances and add them to ball mill B. After ball milling and stirring for 2h, a uniform and transparent polymer solution with a mass fraction of 30.5% is obtained.
[0046] B: Add 50g nickel powder to tank A and 50g nano titanium dioxide to tank B, and stir by ball milling for 48h to fully mix them. The mass fraction of inorganic powder is 58%.
[0047] C: Place the slurry in tank A on a glass plate, adjust the distance between the scraper and the glass plate, and use the scraper to apply the coating to obtain an electrode coating with a thickness of 10-500μm. Place the slurry in tank B on another glass plate, and repeat the above operation to obtain a separator coating with a thickness of 200-800μm.
[0048] D: The above coatings are placed in a water bath and allowed to stand for 4-24 hours, so that the organic solvent DMF in the coatings is fully mixed with water, phase separation occurs, and finally solidified to obtain flexible electrodes and separator green bodies, respectively. The temperature of the water bath is 20°C.
[0049] E: The green body is taken out of the water and dried at 150°C, cut into electrodes and diaphragms of appropriate sizes, and then hot-pressed at 80-150°C and 0.5-10 MPa for 5-10 min to obtain a flexible electrode and diaphragm integrated structure of cathode / diaphragm / anode in sequence.
[0050] Example 4
[0051] A: Weigh 5g of polyethersulfone (PESf) and 25g of N-methylpyrrolidone (NMP) solvent using a tray balance and add them to ball mill A; weigh the same amount of the three substances and add them to ball mill B. After ball milling and stirring for 2h, a uniform and transparent polymer solution with a mass fraction of 17% is obtained.
[0052] B: Add 70g of cobalt powder to tank A and 70g of nano-silicon dioxide to tank B, and stir by ball milling for 48h to fully mix them. The mass fraction of inorganic powder is 70%.
[0053] C: Place the slurry in tank A on a glass plate, adjust the distance between the scraper and the glass plate, and use the scraper to apply the coating to obtain an electrode coating with a thickness of 10-500μm. Place the slurry in tank B on another glass plate, and repeat the above operation to obtain a separator coating with a thickness of 200-800μm.
[0054] D: The above coatings are placed in a water bath and allowed to stand for 4-24 hours, so that the organic solvent NMP in the coatings is fully mixed with water, phase separation occurs, and finally solidified to obtain flexible electrodes and separator green bodies, respectively. The temperature of the water bath is 50°C.
[0055] E: The green body is taken out of the water and dried at 150°C, cut into electrodes and diaphragms of appropriate sizes, and then hot-pressed at 80-150°C and 0.5-10 MPa for 5-10 min to obtain a flexible electrode and diaphragm integrated structure of cathode / diaphragm / anode in sequence.
[0056] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present disclosure (including the claims) is limited to these examples. Based on the concept of the present disclosure, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the embodiments of the present disclosure as described above, which are not provided in detail for the sake of simplicity.
[0057] The embodiments of the present disclosure are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present disclosure should be included in the scope of protection of the present disclosure.
Claims
1. A flexible electrode and diaphragm integrated structure for alkaline water electrolysis, characterized in that: The invention comprises a hydrogen evolution electrode layer, a diaphragm layer and an oxygen evolution electrode layer which are tightly combined and have flexibility through a hot pressing process.
2. The flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 1, characterized in that: The hydrogen evolution electrode layer, the diaphragm layer and the oxygen evolution electrode layer with flexible characteristics are connected in sequence, and finger-like pores or sponge-like pore structures exist in both the electrode layer and the diaphragm layer, and the pore size is 5-50 μm.
3. The flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 1, characterized in that: The thickness of the hydrogen evolution electrode layer and the oxygen evolution electrode layer is 10-500 μm, and the thickness of the diaphragm layer is 200-800 μm.
4. The flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 1, characterized in that: The flexible electrode and diaphragm integrated structure is used for alkaline water electrolysis to produce high-purity hydrogen and oxygen. The prepared flexible electrode and diaphragm can also be used in the field of chlor-alkali industrial electrolysis and flexible batteries.
5. A method for preparing an integrated structure of a flexible electrode and a diaphragm for alkaline water electrolysis, characterized in that: The preparation method comprises the following steps: (1) mixing metal powder or inorganic nano-ceramic powder with an organic solvent containing a high molecular weight polymer by ball milling to obtain a corresponding casting slurry; (2) using a scraper to scrape the tape-casting slurry of step (1) into tape-casting green sheets of different thicknesses; (3) The tape-cast green body obtained in step (2) is immersed in deionized water or ethanol for phase conversion, taken out, dried, and subjected to a hot pressing process to obtain an integrated structure of a flexible electrode and a diaphragm.
6. The method for preparing the integrated structure of flexible electrode and diaphragm for alkaline water electrolysis according to claim 5, characterized in that: The flexible electrode layer material comprises metal powder, inorganic nano-ceramic powder, high molecular polymer, and carbon material; the diaphragm layer comprises high molecular polymer and inorganic nano-ceramic powder.
7. The method for preparing the flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 5, characterized in that: The metal powders mentioned are mostly transition metal powders; preferably, the transition metals include any one or more combinations of nickel, cobalt, iron, manganese, molybdenum, etc., more preferably nickel.
8. The method for preparing the flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 5, characterized in that: The high molecular polymer mentioned is any one or more combinations of polysulfone, polyethersulfone, polyphenylene sulfide, polyaniline, polypyrrole, polythiophene and the like.
9. The method for preparing the flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 5, characterized in that: The mass ratio of the high molecular polymer is 5-20%, the mass ratio of the metal powder is 50-70%, and the mass ratio of the inorganic nano ceramic powder is 10-80%.
10. The method for preparing the integrated structure of flexible electrode and diaphragm for alkaline water electrolysis according to claim 5, characterized in that: The inorganic nano-ceramic powder mentioned is one or more combinations of zirconium dioxide, titanium dioxide, silicon dioxide and the like.
11. The method for preparing the flexible electrode and diaphragm integrated structure for alkaline water electrolysis according to claim 5, characterized in that: In the above step (3), the phase inversion time is 4-24 hours and the drying temperature is 80-150°C.